Biological Assets and Firm Value: Do Fair Value Measurement and Disclosure Matter? - Alfarisyi, Naupal; Diantimala, Yossi; Yahya, Rizal; Saleh, Muhammad (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
This study aims to investigate whether value of biological assets measured by fair value and disclosure of biological assets has influence on firm value. The samples are agricultural companies listed on the Indonesia Stock Exchange between 2018 and 2020 with 51 firm-year observations. Using multivariate analysis, this study found that value of biological assets measured by their fair value has a significantly positive effect on firm value, while the disclosure level of biological assets does have impact on firm value. The control variables, namely profitability, leverage, and growth, significantly affect firm value. This study provides a new perspective and empirical evidence in the research topic because this research focuses on the impact of the application of Indonesian statement of financial standard No. 69 regulating fair value of assets and disclosure of biological assets on firm value.